Development of experimental models of reactivated toxoplasmosis - Bauman, Neda; Srbljanovic, Jelena; Colovic Calovski, Ivana (Medicinski podmladak, 2024)
Toxoplasmosis is one of the most widespread zoonosis worldwide, since Toxoplasma gondii is a ubiquitous obligate intracellular protozoan parasite that infects up to one third of the human population. Although infection is usually asymptomatic in immunocompetent individuals, in vulnerabile categories such as the fetus and immunocompromised patients, toxoplasmosis can lead to severe consequences, in particular congenital and reactivated toxoplasmosis (RT). HAART and global increase in the number of immunocompromised patients undergoing organ and tissue transplantations, in which toxoplasmosis represents important opportunistic infection, shifted the focus of interest from HIV+ patients to transplant recipients. There is an urgent need for identifying novel potent and well-tolerated drugs, since available options for toxoplasmosis chemotherapy are limited, and associated with numerous side effects. Although potential chemotherapeutics are also investigated in vitro, results obtained in in vivo experimental models provide more valuable data. Iatrogenic immunosuppression in mice chronically infected with T. gondii is mostly based on administration of corticosteroids, such as dexamethasone in drinking water and hydrocortisone via subcutaneous injections. In addition, some models involve the use of cytostatics, mainly cyclophosphamide, which is among the most commonly used immunosuppressants in transplantation protocols. Large variations in dosing of immunosuppressants in models of RT call for their optimization. Cytostatics and corticosteroids, applied simultaneously in adequate doses and intervals would allow for simulation of the most frequently applied immunosuppressive regimens in human transplantation medicine. Although there is a variety of in vivo models of toxoplasmosis, a current trend of exponential increase in population of transplant recipients requires a better insight into possible ways of establishing a model of RT. Establishment of a sustainable model of RT would be of great importance in future studies focused on T. gondii infection, and above all, for conducting chemotherapy experiments oriented towards discovery of potential new candidates for the treatment of toxoplasmosis.